Pendalilan Naqli dan ‘Aqli tentang Wujud Allah Menurut al-Ghazali Berdasarkan Kitab Ihya’ ‘Ulum al-Din: Implementation of Naqli and ‘Aqli on the Existence of Allah according to al-Ghazali Based on Ihya’ ‘Ulum al-Din - Hamat, Mohd Fauzi; Shuhari, Mohd Hasrul; Rozali, Muhammad Hafizi; Ali Makdom, Ahmad Hafiz (Afkar: Jurnal Akidah dan Pemikiran Islam, 2021)
Issues related to the existence of Allah the Almighty are important topics for debate, in order to differentiate human beings who are muwaḥḥid (believer) and those who are mulḥid (unbeliever). Any denial and misunderstanding of this concept, will certainly lead to denial and misunderstanding of the existence of Allah the Almighty, and it leads to disbelieving. For this reason, Islamic scholars have paid great attention on these issues, by presenting various arguments and specific evidence of their scholarly works to justify the existence of Allah the Almighty. This paper aims to examine the issues related to the existence of Allah the Almighty from the perspective of a famous reformer (mujaddid) of the fifth century, al-Ghazali (d. 505AH), in his book Iḥyā’ ‘Ulūm al-Dīn. This qualitative study was carried out using content analysis of Iḥyā’. This study found out that al-Ghazali has presented in Iḥyā’ arguments such as al-fitrah, nuṣūṣ and intellect in proving the existence of Allah. This finding shows that al-Ghazali has a strong foundation and argument similar to that of Ahl al-Sunnah wa al-Jamā‘ah, who recognize the nature of using proposition via naqlī and ‘aqlī as the source of evidence on proving the existence of Allah the Almighty.